Insulin concentrations in cerebellum and body balance in diabetic male rats: Aerobic training effects - Arantes, Luciana Mendonça [UNESP]; Bertolini, Natalia Oliveira [UNESP]; de Moura, Rodrigo Ferreira; de Mello, Maria Alice Rostom [UNESP]; Luciano, Eliete [UNESP] (Elsevier, 2013)
Brain insulin has had widespread metabolic, neurotrophic, and neuromodulatory functions and has been involved in the central regulation of food intake and body weight, learning and memory, neuronal development, and neuronal apoptosis. Purpose: The present study investigated the role of swimming training on cerebral metabolism on insulin concentrations in cerebellum and the body balance performance of diabetic rats. Methods: Forty Male Wistar rats were divided in four groups: sedentary control (SC), trained control (TC), sedentary diabetic (SD), and trained diabetic (TD). Diabetes was induced by alloxan (32 mg kg b.w.), single dose injection. The mean blood glucose of diabetic groups was 367 ± 40 mg/dl. Training program consisted in swimming 5 days/week, 1 h/day, 8 weeks, supporting a workload corresponding to 90% of maximal lactate steady state (MLSS). For the body balance testing rats were trained to traverse for 5 min daily for 5-7 days. All dependent variables were analyzed by one-way analysis of variance (ANOVA) and a significance level of p < 0.05 was used for all comparisons. Results: The body balance testing scores were different between groups. Insulin concentrations in cerebellum were not different between groups. Conclusion: It was concluded that in diabetic rats, aerobic training does not induce alterations on cerebellum insulin but induces important metabolic, hormonal and behavioral alterations which are associated with an improvement in glucose homeostasis, serum insulin concentrations and body balance. © 2013 Elsevier Inc.
Keywords: Aerobic training; Body balance; Insulin; glucose; insulin; aerobic exercise; alloxan diabetes mellitus; animal experiment; animal model; animal tissue; body equilibrium; brain metabolism; cerebellum; controlled study; glucose blood level; insulin blood level; male; nonhuman; priority journal; rat; sitting; swimming; workload